Advances in Basic and Clinical Research on Diabetic Foot Ulcers - Wang, Yuqi; Han, Jian; Cao, Qian; Li, Zhi (Journal of Contemporary Medical Practice, 2024)
Diabetic foot ulcer (DFU) is one of the most severe complications of diabetes, involving complex pathological mechanisms such as neuropathy, vascular abnormalities, and infections. In recent years, with advances in treatment technologies and the promotion of multidisciplinary team (MDT) care, DFU diagnosis and treatment have improved significantly. Traditional therapies, including dressings, debridement, and negative pressure wound therapy (NPWT), remain critical in basic treatment. Meanwhile, emerging therapies such as stem cell therapy, growth factor therapy, continuous oxygen diffusion therapy (CODT), and antimicrobial materials offer new hope for treating refractory ulcers. However, DFU's high recurrence rate and poor long-term prognosis remain major challenges, closely associated with blood glucose fluctuations, infections, and psychosocial factors. MDT approaches have significantly improved cure rates and quality of life but face limitations in implementation at primary healthcare levels. Future research should focus on large-scale, multicenter studies with long-term follow-up while strengthening psychological support and personalized management. This would promote comprehensive advancements in DFU diagnostic and therapeutic strategies, ultimately improving patient outcomes and quality of life.